اىفطو فٖ اىشهاوى واىؽػٔن االُخغاة٘ثAdjudicating complaints and electoral appeals - األـخاذ اىٍفاغػ اىػنخٔر ـؽِْم ضٍ٘ػ اىتؽزُشٕ; الٌػرس الٌفاغػ ئارام ُشً اىػَٗ غتػ اىغفٔر (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
There is no doubt that electronice process management turn up through some steps, the organizations or commissions that supervise each steps of election like high and commission in Iraq issuses many decision. Other decisions issuses by the organizations that want to esure about the legitimacy of parliament members after election directly as parliament authority and justice authority organization like Constitution Council at French state. We have many garantes at each steps of election and they are making according to international measures so as to managing the prcess of election independently without any beat down ( violation) and so as to keep the votes, candidates advantage and make the council or parliament that actual representativies of voters and citizens. The competition between parties and candidates of any elections coused to have or exist some garants for prohibiting conflicts between them. So that Legislator trys to make instruments as garants to keep voter’s volition and the rights of parties that participate at election, some of these instruments have un effect upon the process of election when they practices by any parties or candidates as the legal right for them, these instruments called ( Camplaint and appeal). At some states organizations and the commissions that supervise the process of election see that camplaint and appeal of election and legitimacy them, the justice authority participate but not effectively. So we want to return un effective role to justice authority, because it is un legally that organizations or commission supervise the process of election issues decisions and they see complaint or appeal that write aganst these decisions at same time, In another side the nature of see or legitimacy complaints or challenges near to Justice authority function than the nature of Comission election.